Sosialisasi Nilai-Nilai Keselamatan Jalan Raya Di SMKN 2 Kota Makassar - Noor Fadilah Romadhani; Moeh. Kay Muddin Asnur; Muhammad Haristo Rahman; Iriandy; Hartini Ramli (Sakura Digital Nusantara, 2023)
Traffic accidents is a major issue in the aspect of road safety. Based on data from the Directorate General of Road Transportation of the Ministry of Transportation in 2020 that 70% of traffic accident victims come from high school level students. The high number of traffic accident among students means that there is still a lack of awareness of the importance of road safety. This Community Service Activity is in the form of socialization with the theme